(untitled) (Latakia University Journal -Biological Sciences Series, 2019)
أجريت الدراسة على ثلاث ملكات لكل من سلالة النحل السوري A.m.syriaca ولسلالة النحل الإيطالي A. m. lugostica وهجينهما في الجيل الأول F1. أنجزت الدراسة خلال فصل الربيع من عامي 2000-2001 . إن النتائج المتحصل عليها من هذه الدراسة هي : آ- الدراسة الأولى: لبيان عدد القنوات المبيضية في ملكات سلالات النحل الثلاث (السورية والإيطالية وهجينهما الأول) : نتائج التحليل الإحصائي أظهرت فروقاً معنوية بين السلالتين وهجينهما وكان عدد القنوات المبيضية في ملكات النحل الإيطالية أكبر معنوية من السورية والهجين الأول خلال عامي 2000 و2001 (349.70-348.15 قناة ؛ 320.75-321 قناة؛ 335.50-332.50 قناة على التوالي). بينما تفوقت معنوياً ملكات نحل الهجين الأول على السورية . ب-الدراسة الثانية: لبيان عدد القنوات المبيضية لكل من المبيض الأيسر والأيمن في كل سلالة: إن نتائج التحليل الإحصائي أثبتت أنه لا يوجد فروق معنوية بين عدد القنوات المبيضية لكل من المبيض الأيسر والأيمن في ملكات النحل الإيطالية خلال عامي 2000 و2001 (175.45-174.25 قناة و174.40-173.75 قناة على التوالي) ، ولكن وجدت فروق معنوية في ملكات النحل السورية والهجين الأول (161.80-158.95 قناة و161.50-159.50 قناة ؛ 168.55-166.95 قناة و167.70-164.80 قناة على التوالي). ج-الدراسة الثالثة: لمعرفة طول قنوات المبيض الأيسر والأيمن في ملكات سلالتي النحل السورية والإيطالية وهجينهما الأول : اتضح من نتائج التحليل الإحصائي أن طول قنوات المبيض في ملكات النحل الإيطالية أكبر معنوية من ملكات النحل السورية والهجين الأول خلال عامي 2000 و2001 (5.310-5.305 و5.302-5.291 ملم ، 4.598-4.739 و4.614-4.684 ملم ، 4.903-4.915 و4.926-4.946 ملم على التوالي) ، وأيضاً تفوقت ملكات نحل الهجين الأول معنوياً على السورية . د-الدراسة الرابعة: لمعرفة طول القنوات المبيضية لكل من المبيض الأيسر والأيمن في كل سلالة : أظهر التحليل الإحصائي أنه لا توجد فروق معنوية بين طول القنوات المبيضية للمبيض الأيمن والأيسر في ملكات النحل الإيطالية والهجين الأول خلال عامي 2000 و2001 ، بينما وجدت فروق معنوية بين طول القنوات المبيضية للمبيض الأيمن ولم يوجد فروق معنوية بين طول القنوات المبيضية للمبيض الأيسر في ملكات النحل السورية خلال عامي 2000-2001 م . This study examined three queens for each Syrian bee race (A.m. syriaca), Italian bee race (A.m. lugostica) and its first generation hybrid (F1), in the spring season of 2000 – 2001. The results of this study included: A-First study: is to investigate the number of queen ovarioles in the three races of Italian, Syrian and F1 hybrid (produced from the Italian queen and Syrian drones. during of 2000 and 2001 : 1-It could be inconcluded that the number of queen ovarioles is significantly higher in Italian bee race than in Syrian and F1 hybrid races ; whereas the number of the F1 hybrid is significantly higher than that of the Syrian races. 2-The number of main of ovarioles from the Italian to F1 hybrid and Syrian bee races: 349.70 and 348.15 ; 335.50 and 332.50 ; 320.75 and 321.00 ovarioles, respectively . B-Second study: is to investigate the number of ovarioles in the left and right ovary in every race, there were no significantly differences between the number of left ovarioles and right ovaries in the queen of Italian race during 2000 and 2001 (175.45 and 174.25 ; 174.40 and 173.75 ovarioles, respectively), however there were significant differences between the number of left ovarioles and right ovaries in the queen of F1 hybrid and Syrian bee races during 2000 and 2001 (16855-166.95 and 167.70-164.80 ; 161.80-158.95 and 161.50-159.50 ovarioles, respectively) . C-Third study: is to investigate the lenth of queen ovarioles “the left and right ovary” in the three races of Italian, Syrian and F1 hybrid, during of 2000 and 2001: 1-The lenth of queen ovarioles more significant in Italian bee race than it is in F1 hybrid and Syrian races ; but it was more significant in the F1 hybrid compared with Syrian bee races. 2-The main lenth of ovariles from the Italian to F1 hybrid and Syrian bee races is: 5.310-5.305 and 5.302-5.291 ; 4.903-4.915 and 4.926-4.946 ; 4.598–4.739 and 4.614-4.684 m m ., respectively. D-Fourth study: is to investigate the lenth of ovarioles in the left and right ovaries in every race, there was no significant differences between the lenth of ovarioles lift and right ovary in the queen of Italia and F1 hybrid bee races, there was significant differences between the lenth of left ovarioles and right ovaries in the queen of Syrian bee race (during 2000 and 2001).